Hilirisasi produk Smart ENT Unit dinilai sangat bermanfaat bagi mitra Fakultas Kedokteran Universitas Mataram - Hamsu Kadriyan; I Gede Pasek Sutawijaya; Didit Yudhanto (Universitas Mataram, 2023)
Medical technology continues to grows, both for services and education, thus, innovation is needed. One of these innovations is through the development of the Smart Ear Nose and Throat (ENT) Unit, especially for ear, nose, throat, head and neck surgery (ENT-HNS). In the field of education, this can support problem-based learning (PBL) systems. The development of hardware, software and electronic systems is required in the actualization of this Smart ENT Unit. The method for this community service is by transferring the science and technology that has been produced by the authors to partners. This is to support the use of technology that has been developed by academician to partners, namely the Mataram University Primary Clinic. The result of this community service is in the form of handing over a smart ENT Unit to partners. When the equipment is handed over, assistance is also provided to partners regarding the operation and maintenance of the unit. Eventually, the unit has been used to delivering the health service and education. The conclusion of this community service is that the transfer of the Science and Technology Smart ENT Unit has been successfully completed by the authors. Based on the partner testimonials, the benefits have been felt in regards to this program.